Analisis Sengketa Pajak atas Aset Tidak Berwujud Berupa Goodwill di Indonesia - Gusti Ayu Wiharta Mandasari; Siti Nuryanah (Politeknik Ganesha Medan, 2023)
The receiving party in a merger or acquisition can record goodwill, which is subjectively assessed based on appraiser assumptions. Indonesian regulations on goodwill are limited to Article 11A of the Income Tax Law for amortization. Goodwill is almost always a matter of concern between taxpayers, entities claiming amortization, and the tax authority (Directorate General of Taxes). Differences in perception between taxpayers and the tax authority can lead to tax disputes. Tax disputes result in the same losses for both taxpayers and the tax authority. The disputing parties bear high costs (cost of tax compliance and cost of tax collection) to settle tax disputes. This research aims to analyze the causes of tax disputes related to goodwill and recommend solutions to address the recurrence of disputes. This study is a qualitative research with a case study approach. The research is conducted through triangulation, involving content analysis of tax court verdicts from 2018 to 2022 and interviews with tax consultants and the tax authorities. The research findings indicate that there are two main causes of tax disputes related to goodwill. These are differences in the interpretation of tax regulations and the burden of proof related to income generation, maintenance, and collection activities. Based on these findings, the Directorate General of Taxes needs to standardize interpretation differences and harmonize tax regulations to create clear legal certainty that will minimize disputes between the tax authority and taxpayers.